2021
DOI: 10.1007/s42452-021-04650-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimal parameters for fiber Bragg gratings for sensing applications: a spectral study

Abstract: The spectral characteristics viz. reflectivity, bandwidth, and sidelobes’ intensity for uniform and apodized (Gaussian, hyperbolic tangent, apod1, sine, and raised sine) fiber Bragg gratings (FBGs) were studied as a function of grating length and index modulation. The optimal grating length and index modulation to obtain maximum reflectivity and minimum sidelobes were determined, as needed for sensing applications. The impact of various apodization profiles on the spectral response has also been assessed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Therefore, in the end, it comes up with the Pareto front that offers the optimum values of grating parameters for the manufacturing decision makers to select the grating length, grating period, and index modulation by which they can obtain the bandwidth and reflectivity that suit their applications’ requirements. The obtained results are compared to those other studies that yielded the same input parameters for verifying the proposed methods [ 15 , 16 ]. In addition, Thereby, the proposed method’s performance has been validated, the same scenarios are tested using another standard optimization method, such as a genetic algorithm, and a comparison has been conducted.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, in the end, it comes up with the Pareto front that offers the optimum values of grating parameters for the manufacturing decision makers to select the grating length, grating period, and index modulation by which they can obtain the bandwidth and reflectivity that suit their applications’ requirements. The obtained results are compared to those other studies that yielded the same input parameters for verifying the proposed methods [ 15 , 16 ]. In addition, Thereby, the proposed method’s performance has been validated, the same scenarios are tested using another standard optimization method, such as a genetic algorithm, and a comparison has been conducted.…”
Section: Introductionmentioning
confidence: 91%
“…In conclusion, it is a multi-objective optimization problem in which the bandwidth and reflectivity are the optimized variables. Moreover, the grating parameters, including the grating length and modulation index, are the control variables considering the conflict between these objectives for some applications, as noted by surveying a couple of studies [ 15 , 16 ]. These studies reported a positive correlation between the reflectivity and the modulation index on one hand and grating length on the other hand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the refractive index variation is oftentimes illustrated as a square waveform, its shape is better represented by a sinusoidal function [55]. Uniform FBGs (i.e., having constant index modulation and grating period) show undesired sidelobes in the reflected spectrum, which can be reduced through proper apodization profiles of the refractive index [56][57][58]. Monotonically varying the grating period will lead to chirped FBGs [59], whereas tilting the grating planes from their original orthogonal direction with respect to the fiber longitudinal axis will produce a tilted FBG [60].…”
Section: Fiber Bragg Gratingsmentioning
confidence: 99%
“…lation and grating period) show undesired sidelobes in the reflected spectrum, which can be reduced through proper apodization profiles of the refractive index [56][57][58]. Monotonically varying the grating period will lead to chirped FBGs [59], whereas tilting the grating planes from their original orthogonal direction with respect to the fiber longitudinal axis will produce a tilted FBG [60].…”
Section: Fiber Bragg Gratingsmentioning
confidence: 99%